Multi-chamber GEM-based concept of radiated power/SXR measurement system for use in high radiation environment of DEMO. (1st May 2022) - Chernyshova, M.; Dobrut, M.; Jabłoński, S.; Malinowski, K.; Fornal, T.
Abstract: This work describes the progress of development of total core radiation power and soft X-ray (SXR) diagnostic system designed in accordance with the DEMO control requirements. Monitoring of energy loss through the separatrix is necessary for reliable plasma control. Data gathered by this system could also be helpful for studying spatial distribution of heavy impurities, MHD modes and their localization, plasma shape and position. Gas electron multiplier (GEM) technology is assessed as a base for a new radiated SXR power measurement system. The main advantages of this technology are the compactness of GEM detector, good temporal and spatial resolution, the ability to discriminate energy of incident photons and better neutron resilience than existing systems. All of these make it potentially a good candidate for SXR diagnostic system in ITER and DEMO. The scope of the study includes analysis of the feasibility of selected approaches, the design of the diagnostic system, necessary simulations and engineering considerations, and the proposal of an integration scenario. Preliminary design considerations for the GEM-sensor-based system under development have been done. Plasma radiation intensities and spectra have been simulated using data from the appropriate DEMO scenario. A concept of the photosensitive chamber has been assessed. Photoabsorption simulations with the proposed structure and parameters have been conducted and the results have been discussed.